Prospective healthcare students' perspectives and attitudes on pharmacy as a chosen career path - Shadi Doroudgar; Mahsa Sedaghat; Nabeez Noor; Shervin Gorji (Elsevier, 2024)
Background: With the national increase in the number of colleges and schools of pharmacy as well as the decreased pharmacy school applicant pool in recent years, pharmacy school enrollment challenges are at the forefront of issues facing pharmacy programs today. Factors that can influence a candidate's likelihood to pursue pharmacy school are important to evaluate. Recent studies assessing factors that motivate potential pre-health candidates to pursue pharmacy school or other healthcare careers are limited. Objective: To describe prospective candidates' perspectives and attitudes toward pharmacy as a career pathway and assess factors that motivate or deter them from pursuing pharmacy as a career and from considering a specific pharmacy school. Method: The study was cross-sectional and used an online data collection form distributed via the Qualtrics platform from October 4, 2022 through October 12, 2022 using the social media platform Reddit. Reddit has hundreds of subcommunities known as subreddits, that allow for exchange of ideas and discussion regarding various topics. This social media platform is commonly used by pre-health students to discuss career options. The survey consisted of 28 items and two domains, demographics and prospective healthcare students' understanding of responsibilities of pharmacists and their overall perspective on pharmacy as a profession. The survey was targeted toward anyone with an intention of pursuing a health science degree or career. Result: Four hundred participants completed the survey. Participants were mainly Caucasian, male, and with a mean age of 25 years. This study assessed prospective candidates' perspectives and attitudes toward pharmacy as a career pathway, appealing and unappealing characteristics about pursuing a career in the field of pharmacy, and factors that motivate or deter candidates from pursuing pharmacy. While 68 % of the participants had heard that career choices are vast and vary in the field of pharmacy, most still had concerns about the pharmacy field being heavily saturated and lack of job opportunities after graduation. Almost 60 % of responders gained information about pharmacy programs through social media platforms. The North American Pharmacist Licensure Examination pass rate, postgraduate residencies/fellowships, program duration and program reputation were among the top factors in choosing a pharmacy program. Conclusion: Many survey participants had heard that there are a variety of job opportunities in the field of pharmacy, but the majority had heard that the pharmacy field is heavily saturated and that there are lack of opportunities after graduation. Most responders gained information through social media platforms. For prospective pharmacy school candidates, NAPLEX pass rate, number of graduates matched with PGY1 residencies and fellowships, and duration and reputation of the program seems to be among the most important factors in choosing a pharmacy program. Factors that prospective candidates consider when selecting a pharmacy program and the means they use to research about programs can be important considerations for pharmacy programs recruitment. Awareness of the preferences and baseline knowledge of candidates about the field of pharmacy can aid in developing targeted recruitment strategies and informing decision-making in pharmacy programs and recruitment efforts.